2021
DOI: 10.1007/s13272-021-00524-8
|View full text |Cite
|
Sign up to set email alerts
|

T-tail flutter simulations with regard to quadratic mode shape components

Abstract: It is known that the dynamic aeroelastic stability of T-tails is dependent on the steady aerodynamic forces at aircraft trim condition. Accounting for this dependency in the flutter solution process involves correction methods for doublet lattice method (DLM) unsteady aerodynamics, enhanced DLM algorithms, unsteady vortex lattice methods (UVLM), or the use of CFD. However, the aerodynamic improvements along with a commonly applied modal approach with linear displacements results in spurious stiffness terms, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…To study the effect of viscosity and compressibility on the aerodynamic response to structural deformation, the focus is set on an isolated HTP derived from a generic T-tail configuration described in [8,23]. This facilitates studying the aerodynamic response and its dependencies on the displacement amplitude, fluid viscosity, and fluid compressibility without aerodynamic interference effects.…”
Section: Approach and Simulation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the effect of viscosity and compressibility on the aerodynamic response to structural deformation, the focus is set on an isolated HTP derived from a generic T-tail configuration described in [8,23]. This facilitates studying the aerodynamic response and its dependencies on the displacement amplitude, fluid viscosity, and fluid compressibility without aerodynamic interference effects.…”
Section: Approach and Simulation Modelsmentioning
confidence: 99%
“…The airfoil is a symmetric NACA 0012. Previous studies on the generic T-tail have revealed a minimum flutter speed at an incidence angle of 3.0° [23], for which reason this incidence angle was chosen for the presented studies. With a reference surface area of 16 m 2 and the reference values as listed in Table 1, this setting results in an up force and a positive lift coefficient of roughly 0.208 at Mach 0.4 and 0.259 at Mach 0.8.…”
Section: Approach and Simulation Modelsmentioning
confidence: 99%